Analisis Anteseden Dari Sensitifitas Harga Produk Sepatu Di Jakarta - Willy Arafah (Universitas Airlangga, 2010)
This research is consist of the concepts of how do the consumer involvement, consumer innovativeness, brand parity and brand loyalty could affecting the price sensitivity. Questionaires were used as the research instruments to the 150 of people who wearing shoes with brand “ABC” in Jakarta with using purposive sampling method and cross sectional data. Structural Equation Modelling (SEM) analysis system was applied with AMOS software to hypothesized the empirical data. The result shows that there is a significant effect of the consumer involvement to the consumer innovativeness positively that can affecting to the price sensitivity negatively. Brand parity hypothesized proven that it has affected price sensitivity positively and so brand loyalty affecting the price sensitivity negatively. For further research, it’s recommended to extend more objects of study than shoes and add more other variables which are not include in this research.